Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica. Issue 32 (14th November 2022) - Jia, Yu-Lei; Wang, Ling-Ru; Zhang, Zi-Xu; Gu, Yang; Sun, Xiao-Man
Abstract: Owing to the important physiological functions, polyunsaturated fatty acids (PUFAs) play a vital role in protecting human health, such as preventing cancer, cardiovascular disease, and diabetes. Specifically, Yarrowia lipolytica has been identified as the most popular non-conventional oleaginous yeast, which can accumulate the abundant intracellular lipids, indicating that has great potential as an industrial host for production of PUFAs. Notably, some novel engineering strategies have been applied to endow and improve the abilities of Y. lipolytica to synthesize PUFAs, including construction and optimization of PUFAs biosynthetic pathways, improvement of preucrsors acetyl-coA and NADPH supply, inhibition of competing pathways, knockout of β-oxidation pathways, regulation of oxidative stress defense pathways, and regulation of genes involved in upstream lipid metabolism. Besides, some bypass approaches, such as strain mating, evolutionary engineering, and computational model based on omics, also have been proposed to improve the performance of engineering strains. Generally, in this review, we summarized the recent advances in engineering strategies and bypass approaches for improving PUFAs production by Y. lipolytica . In addition, we further summarized the latest efforts of CRISPR/Cas genome editing technology in Y. lipolytica, which is aimed to provide its potential applications in PUFAs production.